Creating personas, performing selves – gazing beyond the masks of drag and neo-burlesque performance - Prince, Lindy-Lee (Faculty of Humanities, 2021)
What if gender is not in the body, but happens to it through a combination of tangible and intangible means – through the coverings that mask, as well as the translations of and on the body? What if gender was malleable? If we cannot break gender, smash it to pieces, then, hopefully we might be able to bend it and fashion it into something that is more useful in the world, desirable, and something functional for an immediate need, or purpose. This thesis introduces the reader to the performance of drag and neo-burlesque, as these take place in bars and nightclubs in Cape Town. I use the concepts of the gaze and the mask in this research to unpack and understand the feminine and hyper-feminine performances by drag and neo-burlesque performers. I argue that contemporary understandings of the “male” gaze, as posited by Laura Mulvey, have become inefficient in addressing the complexities of viewing gendered performances and audience interpretation thereof. I ask the reader to consider how audiences are set up to look at a performance and performing body and what they are meant to interpret about the person, or their character, by looking at the performance. I want to look beyond the stereotypical “male” gaze. I attempt to add to the conversation on objectification in performance, by arguing that the performances that take place on drag and neo-burlesque stages, possess the ability to challenge dominant ideals and social regulations regarding the ways in which gendered bodies ought to perform in public and private space through the prescriptions of a hetero-dominant society. In this thesis I discuss gendered performance, and expression, and the ways in which these performances and expressions work alongside prescribed perceptions of femininity and feminine performance. These prescriptions inform the ways in which individuals are allowed to perform a homogenous idea of gender, and work against gender variance, which in turn, informs the manner in which individuals are allowed to perform sexuality in relation to what is socially mandated and allowed in the heterodominant society. In this thesis, I also explore the creation of the staged performance, and discuss themes of stigma and shame as it is used to discipline those who attempt to perform potentially subversive content in publicly accessible spaces. Further, I explore understandings of beauty and performance, making 7 connections to race, class, and aspirational performance by those who perform drag and neoburlesque in Cape Town. This leads to an exploration of the potential ways in which life outside of the performance might inform the life on stage, and vice versa – asking what is feminine performance, in what ways are feminine performances meant to be viewed, as well as questioning what kinds of feminine performances are socially acceptable?